Consensus making: the state of nature and the nature of the state. The case of the Rocky Mountain Arsenal National Wildlife Refuge - Hippard, Melissa Lynne, author; Murray, Douglas L., advisor (Colorado State University. Libraries, 2007)
The early success of the environmental movement in calling for a substantial shift in state management of natural resources resulted in widespread changes in environmental regulation. However, these structural changes, aimed at maintaining consensus in state-society relations, did not result in a state system capable of effectively integrating public involvement in decision making. While much empirical research in the contemporary practice of collaborative resource management focuses on the practice of democracy, little attention has been paid to how the state's role in balancing competing social priorities structures this practice. The state is a core area of interest in the field of sociology; one important theoretical tradition focuses on how modem, democratic societies rely on the consent of the governed to maintain state legitimacy and power (Weber in Gerth and Mills 1958, Gramsci 1971, Habermas 1976). This qualitative analysis, based on 33 in-depth interviews and extensive document review, was greatly informed by grounded theory (Glaser and Strauss 1967, Strauss and Corbin 1990) and Burawoy's extended case method (1998). The decision-making process at the Rocky Mountain Arsenal reveals how ecological crisis and economic imperatives intersected to create the conditions for a change in the terms of consensus. The roots of contemporary collaborative decision making are found in the case of the Arsenal. In the early 1980s, public trust in the state's ability to respond effectively to environmental crises was low, resulting in a demand for greater involvement in the policy process. Because of the overwhelming uncertainty regarding the level of risk posed by the cleanup and future use of the Arsenal, the traditional command-and-control approach was no longer tenable. Consensus now required alliance building, and social and technical knowledge became the key variables for determining how effective any party to the process could be. Hybrid organizations such as the Restoration Advisory Board, which combine diverse public and state stakeholders, emerged as the means to create positive public perception and supportable policy outcomes.
Keywords: social research; political science; environmental science